2023
DOI: 10.1039/d3dt00479a
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic insight into Pb2+ and Hg2+ ion sensing using cobalt-based coordination polymer in aqueous phase

Abstract: Emissive inorganic-organic hybrid materials open up a new prospect of fast and efficient heavy metal ion sensing in aqueous medium. Here, we demonstrate a highly sensitive Lead (II) ion detection...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…DLS is an efficient technique to explain the uniform dispersibility and particle size of a suspension. , Thus, DLS experiment of the MOF suspension in water was executed (Figure S13). In water, the MOF particles remain monodispersive and the average diameter of the dispersed particles is in the colloidal region (162 nm).…”
Section: Resultsmentioning
confidence: 99%
“…DLS is an efficient technique to explain the uniform dispersibility and particle size of a suspension. , Thus, DLS experiment of the MOF suspension in water was executed (Figure S13). In water, the MOF particles remain monodispersive and the average diameter of the dispersed particles is in the colloidal region (162 nm).…”
Section: Resultsmentioning
confidence: 99%
“…The DLS experiment is a powerful technique to measure the particle size of a suspension . Hence, the DLS experiments of the MOF suspension in the sensing media (water and DMF) were executed (Figure S13) to know the particle size and dispersive nature of the MOF.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The DLS experiment is a powerful technique to measure the particle size of a suspension. 39 Hence, the DLS experiments of the MOF suspension in the sensing media (water and DMF) were executed (Figure S13) to know the particle size and dispersive nature of the MOF. The experiment suggested that in both media, the MOF particles remain monodispersive, and the diameter of the dispersed particles is in the colloidal region.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…S9, ESI †) display that the MOF particles were present in the sensing medium in monodispersed form with an average particle size of 1500 nM. 28,29 After obtaining a stable MOF suspension, 2800 mL of mili-Q water and 200 mL of the MOF suspension were used for all sensing studies. An aqueous solution of 1 mM rifampicin was prepared.…”
Section: Photoluminescence (Pl) Detection Of Rifampicinmentioning
confidence: 99%